Some problems related to primitive maximal dependencies - Thi, Vũ Đức (Journal of Computer Science and Cybernetics, 2016)
This paper gives some results about primitives  maximal dependencies. Some computational problems related to primitive maximal dependencies and antikeys are investigated.